Setting up a market information service - Poon, Bridget (Technical Centre for Agricultural and Rural Cooperation, 2002)
Market information should meet the needs of farmers, in terms of content and format, as well as the frequency and timing of delivery, and the innovative and creative, but most effective means of delivery.